Sustainable Strategies for Managing Domestic Wastewater and Regulating Land Use in Riparian Areas - Jolly Brata Sembiring; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
This study aims to analyze the influence of domestic wastewater management and space utilization control on pests in river-equivalent areas in Lalat Regency. The main problem raised is the low effectiveness of environmental management in the corresponding area due to the increase in domestic activities and its weakness in spatial planning. The approach used is quantitative with multiple linear regression methods. Primary data were obtained through questionnaires to 200 respondents, and secondary data were obtained through documentation studies and field observations. The results of the analysis showed that simultaneously, the five independent variables (environmental management, space availability, community participation, government supervision, and environmental infrastructure) had a significant effect on the habitat in the corresponding area (p = 0.046). Partially, only waste management (p = 0.016) and community participation (p = 0.042) had a significant effect. A determination coefficient (R²) value of 7.5% indicates that the desires of a region are also influenced by other external factors. Based on these findings, it is recommended that the need to improve the household waste management system through the construction of communal WWTP and improve the quality of household septic tanks, as well as community empowerment through the establishment of environmental forums and sustainable sanitation education to support spatial control and poverty in commensurate areas.